Soil water stress and physiological responses of chickpea (Cicer arietinum L.) subject to tillage and irrigation management in lower Gangetic plain - Mukherjee, Subham; Nandi, Ramprosad; Kundu, Arnab; Bandyopadhyay, Prasanta Kumar; Nalia, Arpita; Ghatak, Priyanka; Nath, Rajib (Agricultural water management, 2022)
In India, chickpea (Cicer arietinum L.) is mostly cultivated in post-rice residual soil water on marginal lands. Low crop productivity due to terminal water and heat stress during reproductive stages, is a major concern, especially in the rice-fallows of lower Gangetic plains of India. In this backdrop, we examined the effect of different tillage (CT and ZT) and irrigation management (I0 – no irrigation; IF – irrigation at the initiation of the flowering stage; IPF – irrigation at the initiation of pod formation stage, IF+PF – irrigation at both initiation of flowering and pod formation stage) on the performance of chickpea concerning dynamics of soil and crop water stress affecting various physiological characteristics, yield and water productivity (WP) on an Aeric Haplaquept, clay loam soil in rice-fallows of lower Gangetic plain of India during 2017–18 and 2018–19. ZT with standing rice stubbles modified the hydrothermal regime of the soil by lowering the evaporative loss and vertical movement of soil water within the compacted puddled rice soil and significantly altered the stress intensity faced by chickpea at the critical growth stages. On average, 35.0%, 23.5%, and 15.5% higher soil water storage under ZT as compared to CT during vegetative, flowering, and pod formation stages, significantly alters the plant water status as affirmed by higher relative leaf water content, leaf area index, leaf chlorophyll content, stomatal conductance, and transpiration rate and lowering of proline content and canopy temperature. Application of irrigation at the critical growth stages had a positive priming effect on plant water availability under both the tillage practices. Higher yield (1984 kg ha−1), and WP (13.6 kg ha−1mm−1) under ZT-IF treatment combination proved it to be the best, from the perspective of mitigating terminal soil water stress as well as enhancing the productivity of chickpea in the rice-fallows of lower Gangetic plains of India. •Adoption of ZT improves soil water availability and minimizes the stress intensity.•Supplemental irrigation application can bridge the yield gap of chickpea.•CWSI as a soil moisture stress indicator, has been assessed.•Relation between soil moisture storage and physiological attributes has been established.•An integrated tillage and irrigation management strategy for chickpea has been developed.